Prescription Pattern of Anti-Diabetic Drugs in Type 2 Diabetes Mellitus Patients at a Tertiary Health Care Center, Birgunj, Nepal - Singh, Smita; Yadav, Chandrajeet Kumar; Bhagat, Phulgen; Chakravarthy, Dhivya; Jha, Sudhakar; Mudvari, Anish; Singh, Prabin Kumar; Raut, Kush; Sah, Rohit (Med Phoenix, 2025)
Introduction: Diabetes mellitus has been an emerging public health concern in our country, lifestyle modifications and pharmacotherapy have been the main treatment modality till date. This study was conducted to evaluate the prescription pattern and rational use of anti-diabetic medications.Materials and methods: This cross- sectional study was conducted for three months at National medical college and teaching hospital among 134 type 2 diabetic patients. Socio-demographic data, anti-diabetic medications detail and adherence to the National essential drug list were obtained.  SPSS version 16 was used for statistical analysis.Results: Out of 134 participants, 68 were male and most of the participants (64.17%) were residing in urban area. Hypertension (31.34%) was the most common comorbidity. The number of participants on combination of Biguanides and Sulfonylurea were 38 (28.35%) whereas participants who were only on Metformin was 26(19.40%). The average number of ant-diabetic drugs prescribed per prescription was 1.97.Only single prescription contained a drug prescribed by generic name. Insulin Injections were given to 18(13.43%) patients.Conclusion: The study revealed that Metformin was still the most commonly prescribed anti-diabetic agents both as monotherapy and in combination. Newer agents like DPP-4 inhibitors, SGLT-2 inhibitors have also been used.  Prescribing by generic name was low. Average number of drugs prescribed per prescription was also less.